Electrochemical science and technology : fundamentals and applications - Oldham, Keith B.; Myland, Jan C.; Bond, A. M. (Alan Maxwell), 1946-; Wiley InterScience (Online service) (Chichester, West Sussex, U.K. ; Hoboken : John Wiley & Sons, 2011)
"The book addresses the scientific principles underlying electrochemistry. Starting with the basic concepts of electricity, the early chapters discuss the physics and chemistry of the materials from which electrochemical cells are constructed and the properties that make these materials appropriate as cell components. Much of the importance of electrochemistry lies in the conversion of electrical energy into chemical energy and vice versa; the thermodynamics of these processes is described, in the context of a wide range of applications of these interconversions. An electrode is a surface at which an ionic conductor meets an electronic conductor and the book describes a wide variety of such interfaces, including many non-traditional examples. The structure of the ionic/electronic junction is examined and the reactions that occur there are discussed from molecular, energetic and kinetic viewpoints. Polarizations are phenomena that inhibit the free passage of electricity across electrodes and much of electrochemical research is devoted to understanding these processes and to reducing (or sometimes enhancing) their effect. Electroanalytical chemistry and voltammetric methods are described, but not unduly emphasized, in this text. Where appropriate, the mathematical underpinnings of electrochemical science are described, but the more difficult aspects are presented via the web. Much tangential material is made accessible in a similar fashion, as are answers to the problems that copiously illustrate the material"--Provided by publisher.
Front Matter -- Electricity -- Chemistry -- Electrochemical Cells -- Electrosynthesis -- Electrochemical Power -- Electrodes -- Electrode Reactions -- Transport -- Green Electrochemistry -- Electrode Polarization -- Corrosion -- Steady-State Voltammetry -- The Electrode Interface -- Other Interfaces -- Electrochemistry with Periodic Signals -- Transient Voltammetry -- Appendix -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Electrochemistry; Electrochemistry; Electrodes; Surface chemistry; SCIENCE -- Chemistry -- Physical & Theoretical; Electrochemistry; Elektrokemi; Electronic books